The female signs in Celie's discourses of desire: a psychoanalitic reading of Alice Walker's The color purple - Marín Calderón, Norman David (2007)
This article explores the subjective modes of representation of the protagonist in The Color Purple. It revises the ways how Celie constructs, through diverse personal and communal experiences, her own identity. This construction is possible in virtue of her desire that examines her body and the capacity to transform her own world. This article also shows the ways in which love, oppression, and lack fuse one another in order to build up an authentic female desire in a universe of men. Hence, Celie becomes a text for she engraves in herself several paradigms in relation to her body and her capacity to "see" beyond the restrictive world that surrounds her. This cathartic process demonstrates how the protagonist moves from the paralysis of being an object to the plenitude of being a subject.